Skin Manifestation of Covid-19 Infection - Oiwoh, Sebastine Oseghae; Enitan, Ademola Olusegun (Clinical Manifestations of Covid-19: A Multi-Disciplinary Approach, 2024)
COVID-19 has been shown to have various manifestations across systems but the cutaneous manifestations serve as indispensable clues to the occurrence, and worsening of COVID-19 as well as useful markers for prognosis. Maculopalular manifestations of COVID-19 have been reported to have a higher frequency compared to other manifestations. The severity of COVID-19 can be predicted by the acroischemia in COVID-19 while livedoid eruptions have also been reported to have the highest mortality. For prompt diagnosis, better management and prognosis; intentional attention to the skin through the involvement of Dermatologists is key to better health for the patient.